2015
DOI: 10.1016/j.apgeog.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Cycling willingness: Investigating distance as a dependent variable in cycling behavior among college students

Abstract: We present a novel approach to understanding distance as a barrier to cycling and its use as a dependent variable in multinomial logistic regression. In doing so, this study explores distances in relation to spatially and relevant human factors such as gender and propensity to cycle among college students. College students (N= 949) participated in a health survey and stated possible predictors of cycling based on their cycle usage and preferences in the previous 30 days. While utilizing GIS in a bicycle-friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 65 publications
1
15
0
1
Order By: Relevance
“…For example, Loukopoulos and Gärling (2005) showed that car users may be averse to the physical efforts required by walking, and that travel distance may be an important barrier for use of such active transport. More recently, Millward et al (2013) found that all major walking destinations show strong distance-decay effects: most walks are shorter than 600 metres (m), and very few exceed 1200 m. The analysis of Wuerzer and Mason (2015) suggests that cycling distance appears to be about 3-4 miles among college students. Ferrer et al (2015) identified a minimum walking distance below 10-20 min where trips were very likely to be undertaken walking.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Loukopoulos and Gärling (2005) showed that car users may be averse to the physical efforts required by walking, and that travel distance may be an important barrier for use of such active transport. More recently, Millward et al (2013) found that all major walking destinations show strong distance-decay effects: most walks are shorter than 600 metres (m), and very few exceed 1200 m. The analysis of Wuerzer and Mason (2015) suggests that cycling distance appears to be about 3-4 miles among college students. Ferrer et al (2015) identified a minimum walking distance below 10-20 min where trips were very likely to be undertaken walking.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, survey respondents are likely to have more than average riding experience and skill and so are not necessarily representative of the wider population of cyclists in these countries (cf. [49][50][51]).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other research, the averaged sample may be considered indicative of a more active cyclist population, though the results are not directly comparable due to the "per week" approach in this study (cf. [49][50][51]). Figure 2 shows the distribution of weekly distances, by distance class, for trips to work.…”
Section: Cycling Patterns and Detoursmentioning
confidence: 99%
“…Sehingga, penggunaan sepeda merupakan alat transportasi yang sesuai untuk perjalanan sekolah, terlebih dengan peraturan zonasi sekolah maka dominan jarak tempat tinggal siswa dari sekolah < 5 km (Menteri Pendidikan dan Kebudayaan Republik Indonesia, 2018). Ini merupakan rentang yang efektif untuk penggunaan sepeda (Wang et al, 2018;Wuerzer & Mason, 2015).…”
Section: Pendahuluanunclassified